Analysis of Android Smartphone Usage Preferences compared to iOS - Aritonang, Romaito; Sugara, Igk Adhi; Pane, Sanusi Gazali (Journal Of Accounting Management Business And International Research, 2024)
The development of technology and information is increasingly rapid, the need for access to information regarding technology is also increasingly becoming a basic need for everyone. Internet technology and electronic devices cannot be separated from the rapid development of the times. Smartphone is a tool that provides many applications so that users can develop their knowledge about anything, if they maximize the function of the features and applications in the smartphone. One of them is the operating system. The operating system is the main software that carries out management control over hardware directly. As well as management and controlling other software so that the other software can work. So that a software operating system can work. So a mobile operating system will be responsible for operating the various functions and features available on mobile devices and the widely used operating systems are Android and iOS. The aim of this research is to analyze the differences in smartphone brand preferences in relation to the Android and iOS operating systems, by analyzing the relationship between smartphone features and the choice of smartphone brands based on Android OS and iPhone OS, and the influence between the features offered by the operating system currently used. This is by a smartphone brand with an interest in replacing smartphone devices.